Design and analysis of backward wave folded waveguide travelling wave tube - Fareq, Malek; Stuart, R. A.; Abdullah, B. M. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org